Dear all,

I just want to know the difference between `p(loop)+sqrt(p(loop))-1`

and `p(loop)-sqrt(p(loop))-1`

. Both of them have the quadratic form. Why `p(loop)-sqrt(p(loop))-1`

return an error?

Thanks!

The code is listed as follows.

```
clear;
close all;
clc;
P_max = 1;
cvx_begin
cvx_quiet(true);
variable p(3,1)
variable fes_p
minimize fes_p
subject to
for loop = 1:1:3
p(loop) >= 0
p(loop) <= 1
pow_p(p(loop)+sqrt(p(loop))-1,-1) + p(loop) <= 4
% pow_p(p(loop)-sqrt(p(loop))-1,-1) + p(loop) <= 4 % Why return an error?
end
sum(p) <= fes_p*P_max
fes_p >= 0
fes_p <= 1
cvx_end
```